Sustained Biotic-Abiotic Hybrids Methanogenesis Enabled Using Metal-Free Black Phosphorus/Carbon Nitride - Hu, Andong; Fu, Tao; Ren, Guoping; Zhuang, Minghan; Yuan, Weiqi; Zhong, Sining; Zhou, Shungui (Frontiers in Microbiology, 2022)
Biotic-abiotic hybrid systems (BAHs) constructed by integrating biological methanogens with photocatalysts offer novel approaches for the effective solar-driven conversion of CO2 to CH4, providing significant inspiration for achieving carbon neutrality and alleviating the energy crisis. As metal photocatalysts would cause photocorrosion that damages microbial cells and lead to system imbalance. Therefore, exploring suitable metal-free photocatalysts is of particular importance in the search for more efficient and sustainable BAHs to improve the actual operability and applicability. Herein, black phosphorus/carbon nitride (BPCNx) as an alternative metal-free heterostructure was combined with Methanosarcina barkeri (M. barkeri) to construct M. barkeri-BPCNx hybrid systems, and their cyclic methanogenesis performance was investigated. Our results demonstrated that BPCNx promotes the separation of photogenerated charges and enhances the quantum yield, providing a sustained energy source for the cyclically driven M. barkeri reduction of CO2 to CH4 under visible light. Our system achieved a total CH4 yield of 1087.45 ± 29.14 μmol gcat–1 after three cycles, 1.96 times higher than that of M. barkeri-Ni@CdS. M. barkeri-BPCNx overcame the defects of the metal photocatalyst and kept cell permeability, achieving cyclic stability and effectively maintaining the activity of M. barkeri. These results highlight the viable role of BPCNx as a metal-free photocatalysts in the construction of BAHs for the sustained and efficient methanation of CO2, which is conducive to the development of an environmentally-friendly, low-cost, and efficient strategy for the conversion of CO2 to CH4.